Management Capabilities in Facing Digital Literacy Challenges: A Review - Arina, Ida; Mardiana, Eneng; Sitimariam, Timtim; Widaningsih, Wida; Iskandar, Sofyan (Jayapangus Press, 2025)
In the digital era, school management skills in digital literacy are very important to improve efficiency, productivity, and security. However, many schools still do not have effective management skills in facing digital literacy challenges, such as lack of technology, information, and communication skills. Therefore, efforts need to be made to improve management competencies in digital literacy. The aim of this research is to establish the management skills in facing digital literacy challenges and effective strategies in improving digital literacy skills. This research employs a literature review approach. This study shows that school management skills in digital literacy still need to be improved. The findings of the research show that, Lack of technology, data, and correspondence skills are the main obstacles in improving school management skills in digital literacy, School management needs to improve their skills in using digital technology effectively and efficiently, The need for training and development of school management skills in digital literacy to improve efficiency, productivity, and security. This article contributes to filling the gap in previous studies by providing a systematic review of management skills in facing digital literacy challenges. Thus, can provide practical recommendations for management to enhance digital literacy abilities and elevate education quality in the digital age.